The longest race : a lifelong runner, an iconic ultramarathon, and the case for human endurance - Ayres, Ed (Experiment, 2012)
"Among endurance runners, there are those who have run very long distances, and then there are those who have run very long distances for a very long time. Ed Ayres exemplifies the latter; having run in over 600 races across fifty-five years, he is arguably the most experienced American distance runner still competing today. 'The Longest Race' begins at the starting line of the 2001 JFK 50 Mile--the nation's oldest and largest ultramarathon and, like other such races, an epic test of human limits and aspiration. At age sixty, his sights set on breaking the age-division record, Ayres embarks on a course over the rocky ridge of the Appalachian Trail, along the headwind-buffeted towpath of the Potomac River, and past momentous Civil War sites such as Harpers Ferry and Antietam."--From publisher description.